Potensi Jamur Pangan sebagai Pangan Fungsional untuk Meningkatkan Daya Tahan Tubuh Manusia: Potency of Food Mushroom as Functional Food for Improving the Human Immunity - Yul Harry Bahar; Iwan Saskiawan; Gabriella Susilowati (Politeknik Pertanian Bogor, 2022)
Edible mushroom has important role due to its high protein dan nutrition contents for food substitution. It also has the role as functional food because it has active material contents, comprise of polysaccharide compound (glycan), triterpenoid, nucleotide, mannitol as well as alkaloid, which have benefit function for health and improving the human immunity. This study was conducted in June–September 2020, through secondary data collection, and the analysis by descriptive quantitative approach. The objectives were to: 1) identify the condition of edible mushroom development performance, 2) describe the people preference on food mushroom consumption, 3) describe the potency of edible mushroom as functional food for improving human immunity to protect the Covid-19. The results showed that the development of mushroom as functional food still leave many rooms for improvement. In addition, the production volume should be increased so that it can meet regional demands. Mushroom is known for its nutritional content. Therefore, its consumption rate should be increased as one of the solutions to increase body endurance against viruses and diseases.